Legal Position of Land Tenure in Forest Areas with Special Purposes (Case Study: UB Forest, Tawangargo Village and Donowarih Village, Malang Regency): Kedudukan Hukum Penguasaan Tanah dalam Kawasan Hutan dengan Tujuan Khusus (Studi Kasus: UB Forest, Desa Tawangargo dan Desa Donowarih, Kabupaten Malang) - Kusdinar, Iqbal Firdaus; Wicaksono, Setiawan; Adianto, Daru; Ulum, Muhammad Bahrul (Faculty of Law, Universitas Brawijaya, 2025)
The establishment of the forest areas with specific purposes (KHDTK) is based on the Minister of Environment and Forestry Decision Number 196/Menlhk-PKTL/KUH/PLA.2/1/2020, dated January 22, 2020, regarding the designation of the Educational Forest Area within the protected forest and permanent production forest areas of Kepanjen Forest as the Education and Training Forest of Universitas Brawijaya covering an area of ​​544.74 hectares in Malang Regency, East Java Province. Land tenure within the forest area should be under the Ministry of Environment and Forestry (KLHK) based on the Boundary Marking Minutes. In reality, there is still land tenure within the forest area controlled by the community, where the land is inherited from previous generations and can be used for settlements. Land tenure has been ongoing since the Dutch colonial era in 1919, as confirmed by the Malang Regency Land Office, with the community occupying the location since 1937. The author aims to highlight the legal issues between Sumberwangi Hamlet in the administrative area of Donowarih Village and Sumbersari Hamlet in the administrative area of Tawangargo Village. Considering the history of the formation of Donowarih Village and Tawangargo Village, the establishment history of UB Forest, and the analysis of legal status overlaps between the villages and the UB Forest management, this research conducts a comparative analysis of the settlement regulations, correlating them with land or forest area utilization based on Forestry Law Number 41 of 1999 and Village Law Number 6 of 2014.